Cigarette Smoking Increases the Risk of Type 2 Diabetes Mellitus in Patients with Non-Alcoholic Fatty Liver Disease: A Population-Based Cohort Study - Liu, Chan; Wu, Yanqin; Duan, Wenjuan; Xu, Wenming (Experimental and Clinical Endocrinology & Diabetes, 2022)
Objective Cigarette smoke and non-alcoholic fatty liver disease are risk factors for type 2 diabetes mellitus. However, the impact of smoking on diabetes risk among patients with non-alcoholic fatty liver disease remains unclear.Methods This study included 15,464 Japanese individuals. We defined non-alcoholic fatty liver disease based on abdominal ultrasound findings where excess alcohol intake and other liver diseases were excluded. We used Cox proportional regression analysis to identify risk factors for type 2 diabetes onset.Results During 16,446 person-years of follow-up, 223 of 2,714 non-alcoholic fatty liver disease patients developed type 2 diabetes; the cumulative incidence rate of type 2 diabetes was 13.6 per 1,000 person-years. The proportions of never, former, and current smokers (self-report) were 35.3%, 31.1%, and 33.6%, and 88.5%, 5.1%, and 6.4% in men and women, respectively. In a Cox regression model adjusted for sex, age, body mass index, waist circumference, alcohol intake, exercise, and alanine aminotransferase, aspartate aminotransferase, gamma-glutamyl transferase, lipid profiles, and blood pressure values, relative to never smokers, current smokers with non-alcoholic fatty liver disease had an increased risk of type 2 diabetes (hazard ratio=2.05; 95% confidence interval: 1.43–2.94). In addition, former smoking affected the risk of type 2 diabetes; however, this effect was not statistically significant.Conclusions This longitudinal study showed that current smoking may act as a “second hit” and increase the risk of type 2 diabetes in patients with non-alcoholic fatty liver disease.
Keywords: Cigarette smoking; Type 2 diabetes mellitus; Non-alcoholic fatty liver disease